2002
DOI: 10.1074/jbc.m206792200
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid-induced G1 Arrest and Differentiation Activation Are Associated with a Switch to Cyclin-dependent Kinase-activating Kinase Hypophosphorylation of Retinoic Acid Receptor α

Abstract: Cell cycle G 1 exit is a critical stage where cells commonly commit to proliferate or to differentiate, but the biochemical events that regulate the proliferation/differentiation (P/D) transition at G 1 exit are presently unclear. We previously showed that MAT1 (mé nage à trois 1), an assembly factor and targeting subunit of the cyclin-dependent kinase (CDK)-activating kinase (CAK), modulates CAK activities to regulate G 1 exit. Here we find that the retinoid-induced G 1 arrest and differentiation activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(134 citation statements)
references
References 46 publications
8
126
0
Order By: Relevance
“…Similar to the observation made by the other group, OPG mRNA was inhibited within 24 h (Figure 2f) in the presence of RA (Jacobson et al, 2004). As RARa is a substrate for CAK Wang et al, 2002) and a transcription factor activated by RA, these results suggest that RA-suppressed CAK phosphorylation of RARa links CAK-dependent G 1 arrest to osteoblastic differentiation through transactivation of RA target genes.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Similar to the observation made by the other group, OPG mRNA was inhibited within 24 h (Figure 2f) in the presence of RA (Jacobson et al, 2004). As RARa is a substrate for CAK Wang et al, 2002) and a transcription factor activated by RA, these results suggest that RA-suppressed CAK phosphorylation of RARa links CAK-dependent G 1 arrest to osteoblastic differentiation through transactivation of RA target genes.…”
Section: Resultssupporting
confidence: 89%
“…RA-suppressed RARa phosphorylation is associated with decreased levels of CDK7 and increased expression of differentiation regulators Previous studies have shown that differentiating osteoblastic cells serve as a niche (microenvironment) to mediate granulopoiesis (Taichman and Emerson, 1994;Taichman et al, 1996;Mayack and Wagers, 2008), whereas RA-induced loss of CAK phosphorylation of RARa has a pivotal role in granulocytic differentiation of hematopoietic precursors (Wang et al, 2002(Wang et al, , 2006He et al, 2004;Luo et al, 2007). We therefore examined whether such CAK-RARa signaling also mediates osteoblastic differentiation.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations